Clinical risk factors for underlying gastrointestinal malignancy in iron deficiency anaemia: the IDIOM study - Silva, Angel Castro (Frontline Gastroenterol, 2014)
OBJECTIVE: Ten percent of adults presenting with iron deficiency anaemia (IDA) have underlying cancer. This analysis – the Iron Deficiency as an Indicator Of Malignancy (IDIOM) study – was undertaken to assess whether five simple clinical parameters can usefully predict the likelihood of gastrointestinal (GI) malignancy on subsequent investigation of patients with IDA. DESIGN: Retrospective observational study, with multivariable analysis of the predictive value of sex, age, haemoglobin concentration (Hb), mean red cell volume (MCV) and iron studies for the risk of underlying GI malignancy. SETTING: District General Hospital IDA clinic. PATIENTS: 720 adults with confirmed IDA. RESULTS: Sex, age and Hb were strongly associated with the risk of GI malignancy—the parsimonious model including only these variables yielded ORs of 4.0 (95% CI 2.3 to 7.0) for males compared with females; 3.3 (95% CI 1.7 to 6.4) for age >70 years compared with ≤70 years; and 5.3 (95% CI 2.4 to 11.7) for a Hb of ≤91.4 g/L compared with ≥111.5 g/L. Combining these risk factors identified a subgroup (12% of the study population) at particularly low risk (<2% likelihood), and a second subgroup (16% of the study population) at especially high risk (>20% likelihood) of underlying GI malignancy. CONCLUSIONS: Three simple and objective clinical parameters can be combined to provide a clinically useful cancer risk stratification model for subjects with IDA. This may assist with patient counselling and the prioritisation of investigational resources.